Outcome of Transnasal Endoscopic Repair in Cerebrospinal Fluid Rhinorrhea: A Multicentre Experience from Bangladesh (Community Based Medical Journal, 2025)
Cerebrospinal fluid (CSF) rhinorrhea occurs due to abnormal leakage of CSF through the nasal cavity, often resulting from trauma, surgery, or spontaneous causes. Transnasal endoscopic repair has emerged as the preferred surgical approach due to its minimally invasive nature and high success rates. This prospective, observational study was conducted in four tertiary level specialized institutions in Dhaka, Bangladesh, between April 2023 and September 2024, to evaluate the outcomes of transnasal endoscopic repair of cerebrospinal fluid rhinorrhea. A total of 37 patients diagnosed with CSF rhinorrhea who underwent transnasal endoscopic repair were enrolled in this study through purposive sampling. Data was collected on patient clinical characteristics, site and size of the CSF leaks, surgical techniques, graft materials, and postoperative outcomes. Follow-up was conducted at regular intervals (2 weeks, 1, 3, 4 and 6 months) to assess the success or failure and monitor complications, if any. Trauma (45.90%), iatrogenic (10.80%), and spontaneous rhinorrhea (43.20%) were the main causes, with 49% of participants having chronic conditions. History of preoperative meningitis was present in 8.1% cases. Pre-operative anosmia was present in 27.03% cases. The cribriform plate was the most common leak site (43.2%), and smaller leaks (